Association of arginase 1 gene polymorphisms with the risk of myocardial infarction and common carotid intima–media thickness. Issue 8 (16th March 2007) - Dumont, Julie; Zureik, Mahmoud; Cottel, Dominique; Montaye, Michèle; Ducimetière, Pierre; Amouyel, Philippe; Brousseau, Thierry
Abstract : Background: Recently, it was suggested that arginase (ARG)1 plays an important role in atherogenesis. However, because of its complex functions depending on vascular cell type, its impact on atherogenesis remains unclear. Objective: To evaluate the association between ARG1 polymorphisms and phenotypes related to atherosclerosis. Methods: Among 10 ARG1 polymorphisms selected from databases, 4 single-nucleotide polymorphisms (rs2781666; rs2781667; rs2781668; rs17599586) were tested for association with myocardial infarction (MI) in a case–control study (350 cases vs 581 controls), and with common carotid artery (CCA) intima–media thickness (CCA-IMT) in an independent sample of 963 subjects (Etude du Vieillissement Artériel (EVA) study). Results: The genotype distribution of the rs2781666 G/T polymorphism differed significantly between MI cases and controls (p = 0.005), and the risk of MI was consistently increased for both GT heterozygotes (OR (95% CI) 1.5 (1.1 to 2.0)) and TT homozygotes (OR (95% CI) 2.2 (1.1 to 4.4)). In the EVA study, the rs2781666 polymorphism was also associated with an increase in CCA-IMT (p = 0.010), a surrogate marker of MI. Conclusions: The ARG1 rs2781666 polymorphism was consistently associated with MI and an increased CCA-IMT. These findings reinforce the hypothesis of a significant role of ARG1 in vascular pathophysiology.